2012
DOI: 10.1148/radiol.11110060
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Accuracy of Dual-Source Dual-Energy CT for Noninvasive Determination of Hepatic Iron Accumulation

Abstract: DSDE CT is accurate for diagnosing clinically important hepatic iron accumulation without confounding influence of hepatic steatosis, with diagnostic performance on par with MR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…We also plan to extend the capabilities of our LFQ algorithm to allow for the detection and characterization of iron [83]- [85], which can accumulate in the liver in some forms of liver disease, such as alcoholic liver disease [86]. We will couple this work with a new MMD-based algorithm targeting liver fibrosis and cirrhosis, one of the most outstanding unmet clinical needs in abdominal imaging with CT.…”
Section: Discussionmentioning
confidence: 99%
“…We also plan to extend the capabilities of our LFQ algorithm to allow for the detection and characterization of iron [83]- [85], which can accumulate in the liver in some forms of liver disease, such as alcoholic liver disease [86]. We will couple this work with a new MMD-based algorithm targeting liver fibrosis and cirrhosis, one of the most outstanding unmet clinical needs in abdominal imaging with CT.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a combined phantom and clinical DSDE study, the difference of averaged attenuation between the 140-and 80-kV(p) images was used to differentiate patients with greater than 10% hepatic iron, but similar methods were unable to identify hepatic steatosis in vivo. 24 In a phantom and mouse model of hepatic steatosis, Artz et al 25 demonstrated that attenuation and fat density of the liver parenchyma using unenhanced RSDE correlated highly with phantom triglyceride content, but in the model, only attenuation correlated highly with hepatocyte triglyceride content; the fat material density images did not perform as well. Using novel postprocessing of RSDE monoenergetic image subtraction (termed Dual-energy subtraction imaging [DESI]) in a patient population, Zheng et al 26 were able to identify varying degrees of fat accumulation.…”
Section: Dual-energy Ct Evaluation Of Hepatic Fat Contentmentioning
confidence: 99%
“…Most of the initial reports using dual-source (DSDE) or rapid kilovolt (peak)-switching single-source (RSDE) dual-energy CT for fat quantification in phantom, animal, and human studies have been performed in unenhanced conditions. [22][23][24][25][26] However, given the prevalence of asymptomatic NAFLD and NASH, patients not yet known to have hepatic steatosis often undergo contrastenhanced abdominal CT, without an unenhanced series. The identification and quantification of liver fat content in the post-contrast-enhanced setting using RSDE material density analysis is the topic of this present investigation.…”
mentioning
confidence: 99%
“…Fischer MA et al quantified liver iron content with coexisting fat and also quantified liver fat in the presence of iron and iodine in their ex vivo study with dual-energy CT [16], [17]. In addition, Joe assessed the hepatic iron in liver phantoms and liver transplant recipients by calculating the CT attenuation (HU) difference between high and low tube voltages with DECT [23]. Although they were correlated well with the pathology in their study, however, we believe that the CT value differences in that study reflected mixed information, because the CT values at each tube voltage showed attenuation for both iron and other liver parenchyma (e.g., fat in the liver).…”
Section: Discussionmentioning
confidence: 99%